E2F-1 overexpression correlates with decreased proliferation and better prognosis in adenocarcinomas of Barrett oesophagus. Issue 5 (1st October 2007) - Evangelou, K; Kotsinas, A; Mariolis-Sapsakos, T; Giannopoulos, A; Tsantoulis, P K; Constantinides, C; Troupis, T G; Salmas, M; Kyroudis, A; Kittas, C; Gorgoulis, V G
Abstract : Background: E2F-1 expression is positively associated with tumour growth in oesophageal squamous-cell carcinomas (OSCC), while it exhibits oncosuppressive features in colonic adenocarcinomas (AC). To date there are no data regarding E2F-1 expression and its relationship with tumour kinetics (proliferation, apoptosis) in adenocarcinomas that develop on Barrett oesophagus. Aim: As oesophageal adenocarcinomas occur almost exclusively in the metaplastic Barrett epithelium and the opposing E2F-1 behaviour seems to be cell and tissue-type dependent, we examined the manner in which E2F-1 acts in ACs of Barrett oesophagus. Methods: We estimated the immunohistochemical expression of E2F-1, Ki-67, caspase-3 and p53 immunohistochemical status in 35 Barrett oesophagus ACs. Results: E2F-1 immunopositivity correlated inversely with Ki-67, by semi-serial section and statistical analysis (p = 0.023, Spearman correlation). Semi-serial section analysis revealed a direct association between E2F-1 and caspase-3 staining. No correlation was found with p53 status. Cases with higher E2F-1 immunoexpression exhibited longer survival (p = 0.047, Cox-regression). Conclusions: E2F-1 expression was negatively related to tumour proliferation in ACs of Barrett oesophagus. Additionally, E2F-1 immunohistochemical status correlated positively with patient survival. These findings are opposite from those seen in OSCCs, suggesting that the tumour-suppressing E2F-1 behaviour in oesophageal adenocarcinomas is possibly due to the intestinal-type nature of the metaplastic Barrett mucosa.